2003
DOI: 10.1103/physreva.67.062502
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the polarizability of Na-like silicon by study of the fine structure of high-LRydberg states ofSi2+

Abstract: The fine-structure intervals in the nϭ29 state of Si 2ϩ separating levels from Lϭ8 to Lϭ14 have been measured by microwave spectroscopy. A beam of Si 3ϩ ͑Na-like silicon͒ captures a single electron from an n ϭ10 Rydberg target, forming highly excited Rydberg states of Si 2ϩ near nϭ29. Specific L levels within n ϭ29 are selectively detected by excitation with a Doppler-tuned CO 2 laser, followed by Stark ionization. This allows the detection of microwave induced transitions between different L levels in the nϭ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 13 publications
1
26
1
Order By: Relevance
“…1. Some previous studies have observed significant effects of such stray fields [3]. In contrast, the data in this study showed no indication of stray fields, and the quality of the fit was clearly reduced if a stray field as large as E 2 = 0.0010 (V/cm) 2 was assumed [4].…”
contrasting
confidence: 83%
“…1. Some previous studies have observed significant effects of such stray fields [3]. In contrast, the data in this study showed no indication of stray fields, and the quality of the fit was clearly reduced if a stray field as large as E 2 = 0.0010 (V/cm) 2 was assumed [4].…”
contrasting
confidence: 83%
“…The technique used for this study is similar in principle to that used for a previous study of high-L Rydberg states in Si 2+ [2]. The apparatus used here is a slightly modified version of that used for two recent optical RESIS studies [1,3] and is illustrated schematically in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed in Ref. [2], the reported intervals, in particular the highest (n,L) δE [3] NEW δE [3] TOT δE [4] NEW δE [4] TOT ( (7,9) −0.01 −0.17 −0.00 0.01 (20,9) −0.01 −0.12 −0.00 0.01 L splittings, are influenced by differential Stark shifts that were not considered in Ref. [3].…”
Section: Quantitymentioning
confidence: 99%
“…The value of ⊥ , 1.09(3) • , was found by observing a fine-structure pattern of known scale [7]. The Doppler-tuned laser frequency is given by…”
Section: Spectroscopy Of Rydberg Levels Of Ba +mentioning
confidence: 99%